(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
In this chapter,we focus on the shape preserving approximation using rational polynomials, for rational in _spaces, . In our work, we solve a problem raised by R. DeVore in several lectures for many years ago. It mean we discuss the order of monotone rational approximation for function in , spaces for